2021
DOI: 10.2147/opth.s322166
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Surgical Outcomes Between Ab Interno Suture Trabeculotomy and Ab Externo Metal Trabeculotomy in Adult Patients with Glaucoma

Abstract: Purpose To compare the outcomes of ab interno suture trabeculotomy (AbI-TLO) and ab externo metal trabeculotomy (AbE-TLO) in adult patients with glaucoma aged over 40 years. Patients and Methods A retrospective chart review was conducted, including adult patients with glaucoma who underwent AbI-TLO or AbE-TLO between January 2015 and June 2019. A single surgeon (YO) performed all the operations. Eighty-one patients (81 eyes) were included in this study. Surgical success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…However, Manabe et al [ 21 ] reported that no correlation was present between IOP reduction at 12 months postoperatively and the extent of SC incision. Otori et al [ 22 ] also reported that there were no significant differences in the surgical outcomes and postoperative complication between CT and GATT.…”
Section: Discussionmentioning
confidence: 99%
“…However, Manabe et al [ 21 ] reported that no correlation was present between IOP reduction at 12 months postoperatively and the extent of SC incision. Otori et al [ 22 ] also reported that there were no significant differences in the surgical outcomes and postoperative complication between CT and GATT.…”
Section: Discussionmentioning
confidence: 99%